Soil carbon and nitrogen in unmanaged forests in Southern and Eastern Finland - Kumpu, Atte; Peltoniemi, Mikko; Forsius, Martin; Mäkelä, Annikki (Suomen metsätieteellinen seura, 2025)
Soils have an essential role in ecosystem carbon balance. The soils of natural-like old unmanaged forests have been studied less than those of managed stands. In this study, we collected soil core samples and measured the soil carbon and nitrogen content of 27 old unmanaged forest soils in Southern and Eastern Finland. The results were compared against existing data from managed stands of similar site types. The data was also compared with earlier soil measurements from the same sites to look for any significant changes. The analysis resulted in an average of 2.58, 2.44 and 1.62 kg m-2 of soil carbon and 0.087, 0.097 and 0.074 kg m-2 of nitrogen in the organic layer, 0–10 cm of mineral soil layer and 10–20 cm of mineral soil layer, respectively. Carbon contents in the mineral soil layers were higher in unmanaged forests than in managed forests, but not in the organic-layer. Similarly for nitrogen, there was a significant difference between the unmanaged forests and the managed stands for both mineral soil layers, but not for the organic layer. There were no significant changes in soil carbon or nitrogen contents between the old and new measurements in the old unmanaged forests. The results align with the assumption that carbon and nitrogen content are higher in unmanaged forests than in managed forests due to their higher litter input on average, and more stable and cooler conditions. This means that old unmanaged forests have an important role as carbon storage and that the carbon storage is stable.
Keywords: metsät; boreaalinen vyöhyke; metsäekologia; hiili; ravinteet; boreal forest; mineral soil layer; organic soil layer; maaperä; typpi; hiilen sidonta; kivennäismaat; hiilen kierto; typen kierto; Norway spruce